Successful liver transplantation in common variable immune deficiency with reversal of hepatopulmonary syndrome. Issue 4 (3rd April 2019) - Apostolov, Ross; Sinclair, Marie; Lokan, Julie; Angus, Peter
Abstract : Common variable immune deficiency (CVID) is a primary immunodeficiency disorder that is associated with abnormal liver function tests, however advanced liver disease is uncommon. Hepatopulmonary syndrome (HPS) is a rare but debilitating complication of CVID-associated liver disease. We report a case of CVID complicated by HPS that was successfully treated with orthotopic liver transplant, with the patient recovering to normal hepatic function and successfully weaning off domiciliary oxygen post-transplantation.